Offshore program delivery in a challenging environment: Comparing values of the 'same' students in 'different' locations - Soontiens, Werner (IDP Education, 2005)
Over the past decade Australian universities have successfully delivered programs across Southeast Asia. The emergence of China as a market for education attracts a fair amount of interest and entrance is often seen as a logical extension of a presence in the region. Chinese ethnicity is strongly represented throughout the Southeast Asian region where, apart from the obvious majority in China including Hong Kong, the Chinese ethnic group dominates Singapore. Although a minority group in Malaysia and Indonesia the Chinese ethnic population controls the business sector in these countries. The Chinese population throughout the region is the ‘same’ in that all historically originate from mainland China. In addition, there is a strong heritage awareness and promotion of values and tradition amongst Chinese people, further reinforcing traditional values and behaviour. Forces establishing ‘differences’ in values include different levels of exposure to Western information and values. Hong Kong was managed by the British until the late 1990s, Singapore adopted and embraces Anglo government and bureaucratic systems, regional China has had limited exposure to anything non-Chinese and anything Chinese in Malaysia reflects a minority group that is socially and culturally marginalised. The importance of values from a business education perspective is derived from the impact values have on relationships, groups and organisations. The paper reports on the clustering of values amongst Chinese ethnic business students in Singapore, Malaysia, Hong Kong and China.Data collected on 25 values show that there is a significant overlap between values in Singapore and Malaysia, less so with students in Hong Kong and significantly different from students from mainland China.